SÍNTESE E AVALIAÇÃO DA ATIVIDADE ANTIVIRAL DE DERIVADOS DO SISTEMA 1H-PIRAZOLO[3,4-b]PIRIDINA E DOS SISTEMAS TETRACICLÍCOS 3HBENZO[ b]PIRAZOLO[3,4-h]-[1,6]-NAFTIRIDINAS E 3HPIRIDO[ 2,3-b]PIRAZOLO[3,4-h]-[1,6]-NAFTIRIDINAS. - Azevedo, Alexandre Reis de (2006)
Virus disorders come to long of the years causing a series of upheavals in the different populations. The therapy for the treatment of these illnesses this basing, mainly, in the medicine use and then are in the majority of the cases gotten under the form of synthetic products. This work describes the synthesis of 51 substances, derived from the 1Hpyrazolo[ 3,4-b]pyridine, 3H-benzo[b]pyrazolo[3,4-h]-1,6-naphthyridine systems and of new a 3H-pyrido[2,3-c]pyrazolo[3,4-h]-1,6-naphthyridine system. The synthetic approach involved the preparation of key intermediate 4-chloro-5-carboethoxy-1-phenyl-1H-pyrazolo[3,4-b]pyridine, that after nucleophilic reactions, followed of hydrolysis and chlorocyclization, supplied the desired substances. The derivatives 4-(phenylamino)-5- carboethoxy-1-phenyl-1H-pyrazolo[3,4-b]pyridine (10a-m), 4- (pyridilamino)-5-carboethoxy-1-phenyl-1H-pyrazolo[3,4-b]pyridine (11ae), 4-(phenylamino)-1-phenyl-1H-pyrazolo[3,4-b]pyridine-5-carboxylic acids (12a-m), 4-(pyridilamino)-1-phenyl-1H-pyrazolo[3,4-b]pyridine-5- carboxylic acids (13a-d), 3H- benzo[b]pyrazolo[3,4-h]-1,6-naphthyridines (14a-m) and 3H-pyrido[2,3-c]pyrazolo[3,4-h]-1,6-naphthyridines (15a-c), had been evaluated front the replication of the HSV-1 virus, presenting inhibition around 90%, detaching the derivatives 11d, 11e and 14j, that they had presented resulted, SI of 100000, 10000 and 8571, respectively, that when compared with the Acyclovir, 860, reveals very superior. The evaluation of the activity against the enzime RT, that it is of replication HIV-1 virus of the derivatives 3H-benzo[b]pyrazolo[3,4-h]-1,6- naphthyridines (14a-m) indicated significant activity for the derivatives 14d and 14h, around 41,55 and 43,70%, respectively.The 4-(phenylamino)-1-phenyl-1H-pyrazolo[3,4-b]pyridine-5- carboxylic acids derivatives 12a e 12f had been evaluated front of the Mayaro Virus, presenting inhibition resulted around 90%. The studied derivatives had presented significant a antiviral activity what it means a great contribution in the scientific area for the research in relation to these illnesses.